?IN VITRO PLANT REGENERATION F'ROM ZYGOTIC EMBRYOS OF CITRULLUS LANATUS THUNB - ISLAMAND, R.; AHAD, A.; REZA, M. A.; MAMUN, A. N. K.; JOARDER, O. I. (Biological Sciences - PJSIR, 1995)
A procedure has been developed which allows high frequency plant regeneration from mature zygotic embryos of Citrullus lanatus. Prolific shoot regeneration occurred on Linsmaire and Skoog (LS) medium containing BA-IAA combinations. Embryo axes were more responsive explants than cotyledon explants. Regenerated shoots were rooted on Murashige and Skoog (MS) medium supplemented with 1 mgll NAA.